Resources, barriers, and career influences of former student-athletes - Cadiz, Joaquin Jaime F. 1999-; Guinto, Maria Luisa (Quezon City College of Human Kinetics, University of the Philippines Diliman, 2023)
The experience of being a student-athlete is a unique and presents both opportunities and challenges for student-athletes, and literature on Filipino student-athletes’ experiences and careers is a growing body of knowledge. This study investigated the resources and barriers that 131 former student-athletes from a state university experienced through a survey. The influence of being a student-athlete on the careers of former athletes who pursued a career as a sports professional through interviews. From the survey, the barriers that former student athletes faced were logistical-financial challenges with sports, mental health related concerns and challenges with regards to managing time for their academics. Resources that former student athletes gained were interpersonal skills namely leadership, communication, and teamwork, and intrapersonal skills such as time management, discipline, and adaptability. From the interviews with former athletes the themes for the influences on their careers that were generated were Guidance and Mentorship. Specialization and Expertise, and Creating Opportunities in Sports Recommendations for future studies include first, investigating the experience of former athletes with careers in non-sport related fields. The second recommendation is to investigate the barriers that were reported and how these can become challenges to athletes for their life after sports. The last recommendation is to investigate the culture of former athletes in a narrower criteria and the corresponding resources, barriers, and influences of their experiences.
Vita
Thesis (Bachelor of Sports Science) -- University of the Philippines Diliman
Includes bibliographical references
Keywords: Vocational guidance; College athletes; Career development